(3cJGH TQM OYhI GdCWHGAs - (3CHh GdMSf Ydj Hf gHI Gddg Hf GjROis; (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s ((3TgGH GdOjf GdbOSi s)
(3ChdgG (B:s
(3cfJ cJHJ Edi TjNfG GdCLd Hf GjROi TQM CLhHI GdeSGFd GdJi ChOYgG GdTjN CHh GdMSf Hf HWdGf QMeg Gddg QSGdJg GdehSheI HOYhI GdCWHGA s
(3BNQgG (B:s
(3hfMf fTGgO CcKHQ GdehdhOjf SGYI hdGOJge bHd Cf jZJPhf HGddHf Ch HZjQI jHQRhf TjFkG jejd Edi GdShGO JeJ CLhHI GdeSGFd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B210s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs